Shape effect of elongated soil particles on Discrete Element Modelling of methane hydrate soil sediments - Cheng, YP; Yu, Y; Xu, X; Soga, K (CRC Press, 2014)
Investigations on the geomechanical behaviour of methane hydrate bearing soil has attracted increasing interest, as methane hydrate is a potential energy resource from which methane gas can be extracted in the dissociation of hydrate-bearing sediments. This geomechanical behaviour has impacts on geotechnical issues, such as the stability of the seabed sediment layers and the proximity of wellbores. In this numerical study of Discrete Element Modelling (DEM), triaxial compression tests were simulated to study the behaviour of methane hydrate sediments with two different assumptions on hydrate formation patterns: pore-filling case and cementation case. The soil particles were generated separately using three models: spherical particles and elongated clumps with two different aspect ratios. These were used in order to investigate the influence of soil particle shape on the geomechanical behaviour of hydrate-bearing sediments. Three soil models of different aspect ratios were generated by the same grain size distribution and inter-particle friction. The results of the DEM samples shearing at the same initial void ratio were compared. It was found that the behaviour of methane hydrate soil sediments with elongated shape soil particles seemed to be similar to that of the natural hydrate-bearing sandy sediments retrieved from the Nankai Trough. The stiffness and strength were both enhanced with an increase in aspect ratio. The values of stiffness and strength obtained from the DEM modelling became closer to the experimental results as the aspect ratio of soil particles increased. In addition, the hydrates also strengthened the sediments’ skeleton. Furthermore, it was found that the hydrate growth patterns greatly influenced the hydrate-bearing soil sediments. For the given particle shape, the cementation case gave larger stiffness and strength than the pore-filling case.